2017
DOI: 10.1111/bjh.14807
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12 and CXCR7 are relevant targets to reverse cell adhesion‐mediated drug resistance in multiple myeloma

Abstract: Cell adhesion-mediated drug resistance (CAM-DR) by the bone marrow (BM) is fundamental to multiple myeloma (MM) propagation and survival. Targeting BM protection to increase the efficacy of current anti-myeloma treatment has not been extensively pursued. To extend the understanding of CAM-DR, we hypothesized that the cytotoxic effects of novel anti-myeloma agents may be abrogated by the presence of BM stroma cells (BMSCs) and restored by addition of the CXCL12 antagonist NOX-A12 or the CXCR4 inhibitor plerixaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 54 publications
3
44
1
Order By: Relevance
“…Multiple myeloma benefits from the bone marrow microenvironment (Kim et al ., 2012; Waldschmidt et al ., 2017). It is reported that BMSCs secrete Wnt ligands, which may cause the disruption of Wnt/β‐catenin pathway in MM (Mikesch et al ., 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple myeloma benefits from the bone marrow microenvironment (Kim et al ., 2012; Waldschmidt et al ., 2017). It is reported that BMSCs secrete Wnt ligands, which may cause the disruption of Wnt/β‐catenin pathway in MM (Mikesch et al ., 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Although standard systemic chemotherapy remains the main therapy option, the emergence of clinical drug resistance usually leads to therapy failure (4,25). It has been documented that the bone marrow microenvironment may provide components necessary for cell survival, growth and the development of acquired multidrug resistance (26)(27)(28)(29). This environment consists of hematopoietic cells, stromal cells and the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-clinical models showed that NOX-A12 mobilized white blood cells, hematopoietic stem cells, and progenitor cells in the peripheral blood of mice and healthy human volunteers [ 104 ] and Phase I trials (NCT00976378 [ 187 ] and NCT01194934 [ 188 ]) established its safety profile in healthy volunteers. Pre-clinical models demonstrated that co-treatment of multiple myeloma (MM) cells with NOX-A12 inhibited chemotaxis of MM to bone marrow, inhibiting cell adhesion-mediated drug resistance and sensitizing them to chemotherapy [ 189 ]. NOX-A12 also decreased BM niche microenvironment receptivity to MM cells, halting an essential step in disease progression in mouse models [ 190 ].…”
Section: Clinical Trials Of Aptamer Application In Oncologymentioning
confidence: 99%